Musa Paradisiaca derived intrinsically heteroatom doped carbon dots as antioxidant and controlled drug release behavior - Samiah A. Alhabardi; Jawza A. Almutairi; Gadah A. Al-Hamoud; Zainab Zaki Zakaraya; Umme Hani; Zahrah Ali Ahmed Asiri; Islam Al Freahat; Walaa Alsafadi; Wael Abu Dayyih; Sharuk L. Khan; Md. Zamshed Alam Begh (PLoS ONE, 2025)
This work presents a green, single-step hydrothermal synthesis of intrinsically nitrogen-doped Carbon dots (MCDs) derived from Musa paradisiaca, a low-cost and renewable biomass source. The eco-friendly synthesis avoids external dopants or harsh chemicals, offering a scalable and sustainable alternative to conventional multistep methods. The resulting MCDs, with an average particle size of 4.2 nm (TEM), display desirable surface functionalities (FTIR, XPS) and heteroatom doping. Optical characterization revealed a broad UV-vis absorption at 280 nm and strong blue photoluminescence at 440 nm. DLS and zeta potential measurements confirmed excellent colloidal stability. The MCDs demonstrated high antioxidant activity (>80% radical scavenging) and biocompatibility in cellular assays. Moreover, they enabled controlled drug release, underlining their promise as multifunctional nanocarriers. Given their green synthesis, stability, and performance, these MCDs are highly suitable for future biomedical and clinical applications, particularly in antioxidant therapy and targeted drug delivery.